Reading Wittgenstein with Anscombe, going on to ethics - Diamond, Cora (Harvard University Press, 2019)
Reading Wittgenstein with Anscombe, Going On To Ethics is a collection of seven essays, divided into three parts. The essays bring out connections between Wittgenstein's thinking and questions of continuing interest in the philosophy of language, logic, and ethics. A dialogue with Anscombe runs through the essays, which take up questions about how we should respond to thinking that has miscarried or gone off the rails. The main issues discussed in this book concern how we are to understand thoughts, forms of words, and uses of language that seem crucially important to our understanding or self-understanding, but cannot fit in the template we instinctively bring to bear on questions about how language and thought are related to reality. The book presents Wittgenstein as a responsive philosopher, and it does this through a continuing dialogue with Anscombe.--